DEMOGRAPHIC DISTRIBUTION OF MAXILLOFACIAL FRACTURES IN AYUB TEACHING HOSPITAL: 7-YEAR REVIEW - Abbas, Iram; Fayyaz, Muhammad; Shah, Irfan; Khan, Muhammad Ayub; Qazi, Sadia Haleema; Munir, Nadia; Bibi, Ayesha; Abbasi, Masroor (Journal of Ayub Medical College Abbottabad, 2009)
Background: This retrospective study was carried out to determine the demographic distribution of Maxillofacial Fractures (MFF) in patients reported to Maxillofacial Surgical Unit, Ayub Teaching Hospital, Abbottabad from 2001 to 2007. Methods: All the patients having a history of maxillofacial fractures were included according to age, gender distribution and risk factors. Isolated Nasal fractures, Naso-Orbito-Ethmiodal complex fractures and earthquake victims were excluded from this study. Results: This study encompassed a total numbers of 952 patients. Males were 645 (67.8%) and females were 307 (32.2%) with male to female ratio 2.1:1. Most of the fractures occurred during third decade of life. The most common risk factor was Road Traffic Accident (RTA) n= 70 (38.9%). Most of the fractures were occurred during the month of June, July and August. Conclusion: RTA is still the most common risk factor of maxillofacial fractures and is more common in male. Keywords: Maxillofacial fractures, Facial fractures and its risk factors, Maxillofacial trauma